Haemostasis with fibrin glue injection into the pericardial space for right ventricular perforation caused by an iatrogenic procedural complication. (17th May 2016) - Arai, Hirofumi; Miyamoto, Takamichi; Hara, Nobuhiro; Obayashi, Tohru
Abstract : An 89-year-old woman with severe aortic valve stenosis and bradycardia presented with circulatory shock due to cardiac tamponade. We performed pericardiocentesis, and then diagnosed right ventricular perforation by echocardiography with microcavitation contrast medium just before inserting a drainage tube. We then inserted the drainage tube in the appropriate position and withdrew blood-filled fluid. The patient was haemodynamically stabilised, but haemorrhage from the perforation site continued for a few days. We injected fibrin glue into the pericardial space through the drainage tube and achieved haemostasis. Thus, we avoided surgery to close the perforation in this high-risk patient. There was no recurrence of haemorrhage. She subsequently had elective aortic valve replacement at another hospital. No adhesions in the pericardial space were seen during surgery.